Minimal wave speed of traveling wavefronts in delayed Belousov-Zhabotinskii model - Shuxia Pan; Jie Liu (Electronic Journal of Qualitative Theory of Differential Equations, 2012)
This paper is concerned with the traveling wavefronts of Belousov-Zhabotinskii model with time delay. By constructing proper upper and lower solutions and applying the theory of asymptotic spreading, the minimal wave speed is obtained under the weaker condition than that in the known results. Moreover, the strict monotonicity of any monotone traveling wavefronts is also established.